OPTIMALISASI LAYANAN BIMBINGAN DAN KONSELING MELALUI INOVASI DIGITAL: TEMUAN FIELD STUDY di MTS NEGERI MODEL SAMARINDA - Siti Hafidhoh; Bahrani; Sudadi (STKIP Subang, 2025)
This study aims to describe the implementation of educational management and the effectiveness of Guidance and Counseling (GC) services at MTs Negeri Model Samarinda through a field study approach. The field study was carried out from September to November 2025 through direct observation, in-depth interviews, and document analysis to examine the application of the eight National Education Standards (SNP) as the core framework for evaluating the school’s managerial practices. The findings show that MTs Negeri Model Samarinda has implemented systematic educational management, including needs-based program planning, clear task organization, disciplined and innovative learning processes, and continuous supervision through academic and non-academic monitoring. The school’s facilities are generally adequate, although some areas still require enhancement. Financial management operates transparently and accountably, supported by government funding and contributions from the school committee. The Guidance and Counseling unit functions actively in providing student support, as indicated by frequent student visits for various academic and personal concerns. However, the study also reveals that some students remain reluctant to access GC services due to fear, embarrassment, or the perception that counseling is only for problematic students. This situation highlights the need for more inclusive and accessible counseling mechanisms. As a follow-up, the study recommends developing a web-based Management Information System (Web Counseling) as an alternative digital platform that is safe, flexible, and capable of reaching all students effectively. Overall, the study offers a comprehensive overview of educational management practices within the school while proposing an innovative solution to improve counseling accessibility. These findings are expected to provide practical contributions for strengthening service quality and enhancing educational management in the future.